Response to SARS-CoV-2 vaccination in systemic autoimmune rheumatic disease depends on immunosuppressive regimen: a matched, prospective cohort study. Issue 7 (18th March 2022) - Mandl, Peter; Tobudic, Selma; Haslacher, Helmut; Karonitsch, Thomas; Mrak, Daniel; Nothnagl, Thomas; Perkmann, Thomas; Radner, Helga; Sautner, Judith; Simader, Elisabeth; Winkler, Florian; Burgmann, Heinz; et al.
Abstract : Objective: To assess the humoral response to messenger RNA (mRNA) vaccine of patients with systemic autoimmune rheumatic disease (SARD) and the effect of immunosuppressive medication in a matched cohort study. Methods: Patients with SARD were enrolled and matched 1:1 for sex and age with healthy control (HC) subjects. Differences in humoral response to two doses of an mRNA vaccine in terms of seroconversion rate (SCR) and SARS-CoV-2 antibody level between the two groups and the impact of treatment within patients with SARD were assessed. Results: We enrolled 82 patients with SARD and 82 matched HC. SCR after the first dose was lower among the patient group than that of HC (65% compared with 100% in HC, p<0.0001) but levelled up after the second dose (94% vs 100%). After the second dose, SCR was lower for patients on combination disease-modifying antirheumatic drug (DMARD) therapy compared with all other groups (81% compared with 95% for monotherapy, p=0.01; 100% for both no DMARD therapy and HC, both p<0.0001). In addition, antibody levels after both doses were lower in patients compared with HC. We found that vaccination response was determined primarily by the number of DMARDs and/or glucocorticoids received, with patients receiving combination therapy (dual and triple therapy) showing the poorest response. Conclusions: Patients with SARD showed a good response after the second vaccination with an mRNA vaccine. However, the choice of immunosuppressive medication has a marked effect on both SCR and overall antibody level, and the number of different immunomodulatory therapies determines vaccination response.